2018
DOI: 10.1002/pbc.27485
|View full text |Cite
|
Sign up to set email alerts
|

Hope and benefit finding: Results from the PRISM randomized controlled trial

Abstract: Background: Adolescents and Young Adults (AYAs) with cancer are at risk for poor psychosocial outcomes, perhaps because they have not acquired skills to navigate adversities of illness. In a recent phase II randomized controlled trial (RCT), the “Promoting Resilience in Stress Management” (PRISM) intervention was associated with improved patient-reported resilience, quality of life and distress. In this planned analysis of secondary aims, we hypothesized PRISM would also improve targeted coping skills of hopef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 45 publications
2
83
0
Order By: Relevance
“…The PRISM intervention has been successfully researched in other AYAs with serious and chronic illnesses such as cancer and diabetes, in which the diagnosis is usually established later in life . On the other hand, the diagnosis of CF is usually established during infancy and it is one of the most common life‐shortening diseases with increased morbidity which might reflect to their emotional status very early in life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISM intervention has been successfully researched in other AYAs with serious and chronic illnesses such as cancer and diabetes, in which the diagnosis is usually established later in life . On the other hand, the diagnosis of CF is usually established during infancy and it is one of the most common life‐shortening diseases with increased morbidity which might reflect to their emotional status very early in life.…”
Section: Discussionmentioning
confidence: 99%
“…The promoting resilience in stress management (PRISM) intervention is a brief, disease nonspecific, skills‐based intervention developed for AYAs with chronic or serious illness. PRISM has demonstrated feasibility among populations of AYAs with cancer and diabetes, and a phase 2 randomized controlled trial comparing PRISM to usual care among AYAs with cancer suggested PRISM is also associated with higher patient‐reported resilience, quality of life, hope, and benefit‐finding, and with lower risk of psychological distress 6 months after enrollment …”
Section: Introductionmentioning
confidence: 99%
“…Eligible participants for the phase II, parallel, 1:1 RCT were enrolled between January 2015 and October 2016. Participants provided written informed consent, and the Seattle Children's Hospital Institutional Review Board approved this study (IRB protocol no.…”
Section: Methodsmentioning
confidence: 99%
“…Promoting Resilience in Stress Management (PRISM) is a novel, brief, developmentally appropriate, skill‐based intervention targeting the “resilience resources” of stress management, goal setting, cognitive reframing (evaluating and reappraising negative cognitions and self‐talk), and benefit finding (finding meaning and benefit from adversity) . In a phase II randomized controlled trial (RCT) testing the efficacy of PRISM compared with psychosocial usual care (UC) in AYAs with cancer, PRISM was associated with improved patient‐reported resilience, hope, benefit finding, and cancer‐specific quality of life and decreased psychological distress …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation